Brain Arteriovenous Malformations: Diagnostic Challenges and Therapeutic Options - Maurae, Perlin Nigel Valencia; Hakim, Baiq Sheila Oktalia; Yuar, Alana Akmal (Jurnal Biologi Tropis, 2025)
AVMs involve complex hemodynamic disturbances, including vascular steal and venous hypertension, as well as molecular underpinnings such as mutations in the KRAS, ENG, or ALK1 genes that trigger dysregulation of angiogenesis and endothelial-mesenchymal transition (EndMT). This literature review aims to comprehensively analyze the pathophysiological aspects, diagnosis, and current therapies for brain AVMs, including the development of targeted therapies such as MEK inhibitors and anti-VEGF, as well as their clinical implications in reducing bleeding risk and improving patient outcomes. This literature review was conducted using a systematic literature review method through searching scientific articles and references related to brain arteriovenous malformations (AVMs). The results of the literature study show that brain arteriovenous malformations (AVMs) are congenital vascular abnormalities characterized by abnormal connections. With an incidence of 1.34 per 100,000 person-years, AVMs are often asymptomatic until complications arise, with bleeding being the primary presentation in 50% of cases. Diagnosis requires multimodal imaging (CT/MRI/DSA) and the Spetzler-Martin classification to assess therapeutic risk. Treatment includes a multimodal approach: microsurgery (effective for small, non-eloquent AVMs), radiosurgery (staged obliteration with risk of edema), and embolization (as adjuvant therapy). The discovery of genetic mutations (KRAS, ENG) and dysregulation of signaling pathways (TGF-β/VEGF) opens the door to targeted therapies such as MEK inhibitors or anti-VEGF. Multidisciplinary collaboration and an understanding of the molecular pathophysiology are key to improving patient outcomes. In conclusion, brain AVMs represent a complex clinical challenge that requires an integrated understanding of pathophysiology, accurate diagnosis, and risk-based therapeutic strategies.